Revelation as an Epistemic Basis: An Examination of Authenticity and Its Implications for the Reconstruction of Modern Islamic Education - Jumrotunisak Jumrotunisak; Hamdanah Hamdanah; Mazrur Mazrur (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The world of Islamic education today faces the problem of dualism in knowledge, namely between religious knowledge and modern knowledge, which results in the learning process lacking a complete epistemological foundation. This study emphasizes a single, solid foundation, namely revelation as an epistemological basis capable of collaborating the two. This study focuses on highlighting the authenticity of revelatory texts and their implications for the renewal of modern Islamic education through a literature study using descriptive-analytical methods. The results show that the authenticity of revelation provides a strong foundation and guidance on values and methods for building a more comprehensive and relevant Islamic education. The integration of revelation with modern disciplines encourages the emergence of an educational paradigm oriented towards character, rationality, and technological advancement without abandoning spiritual values. This study confirms that revelation can be a strong foundation in designing an adaptive, superior, and responsive Islamic education system to the challenges of modern civilization, with the hope of producing Muslim scientists who are moral, have integrity, and are able to respond to global challenges.